Model Pembelajaran Intergratif Dalam Pendidikan Anak Usia Dini di Era Digital - Muvid, Muhamad Basyrul (Program Studi Pendidikan Islam Anak Usia Dini STAI YPBWI Surabaya, 2023)
Early childhood education is a process to educate children to mingle, imagine and be creative to the fullest. To answer this, an integrative learning model is needed so that it can really maximize learning so that the learning objectives can be achieved. The research method in this study uses library research with interpretive analysis techniques. The result obtained is that PAUD must become an educational institution that can lead students to become a generation that has character, creativity and understands digital progress, of course with all the problems that exist in each PAUD, especially facilities (internet). However, this can be overcome by introducing students to new learning resources, namely those that come from electronics, in addition to books and pictures. This is an educational step that learning resources are not only paper (books) but also other forms (electronic media). Thus, integrative learning does not only emphasize offline or online, but also teaching methods and children's learning styles that are not only one direction or one source, but two directions, many sources so that children's imagination and creative power can develop more.